Intérêt de drainage prophylactique en chirurgie digestive : étude prospective au service de chirurgie générale de l’hôpital mixte de Laghouat - BOUCHEMAL Samira.; BOUAICHA Sara (My University, 2023)
This is a prospective, monocenter, comparative and analytical cohort study, which is conducted in the general surgery department at the mixed hospital of Laghouat, conducted over a period of 06 months, involving 114 patients operated for a digestive pathology classified II, III and IV of ALTEMIER, of which 56 patients did not benefit from PD and 58 patients benefited from PD at the end of the intervention. The main objective of our study was to assess the value of PD in digestive surgery at risk of CPO. The mean age of our study population was close to 36 years, with a male predominance (64.9%), appendicular abscess was the most frequently treated pathology in our series, followed by appendicular peritonitis, with an average operating time of 01.69h. and an estimated average length of hospital stay of 05.89 days. The inferential analysis comparing the two groups mentioned above revealed significant results, particularly in terms of: length of hospitalization, duration of postoperative antibiotic therapy, patient lifting, duration of the nasogastric and urinary tube, resumption of feeding and duration of antibiotic prophylaxis The total rate of CPO in our study was of the order of 28/114 cases or 24.56. Including 13 cases in the undrained group and 15 cases in the drained group. In addition, we found 14 cases of deep CPO, and 11 cases of positive PD, . The ratio of positive PD to number of deep CPOs is estimated at 78.57% which represents the sensitivity rate of PD in the detection of deep CPOs in our study. Overall, our study highlights the interest of prophylactic surgical drainage in digestive surgery for the diagnosis of postoperative complications. While CT and abdominal ultrasound are commonly used diagnostic tools, they present certain limitations in the limited resources of developing countries, hence the importance of this diagnostic, therapeutic and prophylactic means
70p.